TOTAL PHYSICAL RESPONSE METHOD IN FOREIGN LANGUAGE LEARNING - Rahman, Yunanfatur (ELTICS : Journal of English Language Teaching and English Linguistics, 2017)
Foreign language is now a must in every level of education. People begin to listen to foreign language and the try to master it. Listening is the language skills that are closely related to the daily life of human beings. Listening is the process of accepting verbal symbols with caring, understanding, appreciation, and the interpretation of information, here we capture the content or messages, as well as to understand the meaning of communication. While listening to a foreign language we will hear how the language is spoken. Therefore, listening is a basic skill that must be mastered by learners in learning a foreign language before speaking, reading and writing skills. But in fact, the foreign language learners have difficulties in Listening. The Total Physical Response method can desirable overcome this problem. Â  Key words : methods, Â listening skills, foreign language